The risk of increased daytime sleepiness and obstructive sleep apnea among the group of professional drivers - Bąk, Ewelina; Napierała, Jolanta (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Obstructive sleep apnea (OSA) is the most common clinical problem in the group of diseases classified as sleep breathing disorders. Professional drivers are a group that is particularly exposed to the consequences of OSA during the day. This is a very significant problem as chronic daytime sleepiness and falling asleep at the wheel are now recognized as one of the leading causes of road accidents caused by drivers.The aim of the study was to assess the risk of excessive daytime sleepiness and obstructive sleep apnea among the group of professional drivers. Material and methods: The research group consisted of 101 people employed as a professional driver. In order to assess excessive daytime sleepiness and the risk of obstructive sleep apnea, the Epworth sleepiness scale, the Berlin Questionnaire and the self-questionnaire were used. Results: Among 45 drivers (44.6%) had a high risk of OSA using the Berlin Questionnaire, and 56 drivers (55.4%) had a low risk of OSA. According to the Epworth sleepiness scale, it was found that 19.8% of drivers experienced mild daytime sleepiness and 13.9% were drivers with excessive daytime sleepiness require medical consultation. In drivers with a high risk of OSA, the relationship with increased excessive daytime sleepiness was confirmed in the Berlin Questionnaire (85.7%). Conclusions: Among professional drivers, the risk of developing obstructive sleep apnea increases due to risk factors. There is a relationship between excessive daytime sleepiness and risk factors for obstructive sleep apnea.